Digital Savvy: Know the Technology, Be Aware of the Dangers - Feri Alpiyasin; Hasanah Tisna Amijaya; Ganjar Nurul Fajar; Jajat Sudrajat; Muhamad Firza; Putri Alivia Nur Khalizah; Trisna Saputra; Naia Aulia Fitria; Angel Savira Pricillia Pratama; Thazkia Listi Alistianti; Alya Nazhara Nurseptia; Moch Rival Mulyadi; Ghaida Nafisyah; Syahril Fathan Sailendani; Allya Azkya Subarja; Elsa Wirda Saputra (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2025)
The community service initiative titled "Digital Smarts: Understanding Technology and Its Risks" seeks to examine the difficulties encountered by pupils at Miftahul Huda Al Azz Junior High School regarding their utilization of digital technology and the related hazards. The primary concerns highlighted encompass insufficient awareness of potential hazards, including online fraud, identity theft, and adverse effects on mental well-being. This community service initiative employed a socialization approach that included a pre-test, a presentation of the material, a post-test, and an evaluation of the activities. The findings indicated that numerous students were ill-equipped to confront threats in the digital realm, despite their significant dependence on technology. The conclusion from this community service initiative is that training programs aimed at improving understanding of technology and its associated risks are crucial for cultivating students into more informed and proactive digital users, thereby facilitating safer technology use.